(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The goal of this esearch was to analyze the impact of Neurobic Exercise on the Memory Enhancement in the Elderly individuals experiencing Disease. Amid January to September 2012, twenty two female more seasoned grown-ups experiencing disease who were living at Mitraparpsongkoh Foundation, Pathum Thani Province in Thailand, were purposively chosen to take part in this research. Chosen participants were engaged with Neurobic Exercise Program on each 2 days continuously for about a month. The instruments comprised of a Demographic Data Form, the Mini-Mental State Examination-Thai 2002, the Memory test and a Neurobic Exercise Program. The dependability of the Mini-Mental State Examination-Thai 2002 and the memory test utilizing Kuder-Richadson 20 were.89 and .81 individually. Information were dissected utilizing elucidating insights and Paired t-test. The outcomes uncovered that the normal memory scores of the trial amass subsequent to getting the Neurobic Exercise Program were factually and altogether higher than before accepting the Neurobic Exercise Program at a dimension. The consequences of this examination could be utilized as rules by human services suppliers in improving the memory maintenance of the elderly individuals experiencing disease and postponing the weakening of the brain.